THE QUALITY MANAGEMENT OF ACADEMIC SERVICES AT UNIVERSITY (The Study Of Two Universities In Jambi) - Jamaluddin, Mr (Reflective, 2013)
This research was based on the philosophy of Total Quality Management at university using the theory of quality management, and the concept of Service Quality. It was a qualitative inquiry which took two universities in Jambi, namely The Jambi State University and the State Institute for Islamic Studies considering their quality management systems. The study revealed that the quality management of both universities services was not optimum yet, particularly the studentsâ satisfaction. Those were indicated by these factors. First, planning was not based on the market research and environment scanning. Second, quality assurance department tend to be bureaucratic, low coordination, inconsistency between the blueprints and application, and incompetence human resources. Third, the implementation of academic services was not good yet in all aspects such as service quality, particularly due to delivery, emphaty, and reliability. Meanwhile, the evaluation of service quality management did not emphasize on corrective and preventive actions. I found out some critical inhibitor factors of the service quality management on these two universities; (1)âcultureâ including disorganized habits, formalistic, and instant; (2) mindset of the management and academic staff ; (3) inconsistency and materialism mental attitude; (4) instructions rather than communication, (5) and lack of quality control system. The studentsâ academic satisfaction were inlfluenced by two factors; (1) the students perception on core service; (2) the students-teacher intraction. The implication of the study as follows.(1) Lower management should be involved in formulating strategic planning. (2) The lecturers should be empowered through some training to change their working culture, as well as mindset and mental attitude. (3) The academic content should be up dated based on customersâ need as well as sains and technology. (4) Evaluation and monitoring should be followed by corrective and preventive action.Keywords: quality management, academic services, university, Jambi.